Penerapan Model Pembelajaran Group Investigation Pada Materi Organ Pernapasan Manusia Berbasis Lesson Study Kelas V SDN Mojolangu 3 Malang - Weryanti Laen Langi' (LPPM UKI Toraja, 2021)
This paper aims to describe the application of the Group Investigation (GI) learning model to the material of human respiratory organs in class V. This study aims to understand students about the human respiratory organs, the functions of the human respiratory organs, and how to care for the respiratory organs. This learning is based on lesson study with the following stages: (1) planning (plan), (2) implementation (do), (3) reflection (see). The approach used is a qualitative descriptive approach, to describe the activities of teachers and students that occur during the implementation of learning. This learning was carried out at SDN Mojolangu 3, Malang City with the subject of 42 grade V students and a model teacher. The results of the application of the Group Investigation learning model are able to foster a sense of responsibility, train good cooperation between students in group work, and increase student activeness in learning activities.